Screening of sensitivity to mandipropamid of Plasmopara viticola populations from Italian vineyards by molecular and biological methods. (11th August 2016) - Nanni, I.M.; Pirondi, A.; Contaldo, N.; Collina, M.
Abstract: The objective of this work was to study the sensitivity to mandipropamid of 33 Plasmopara viticola populations utilizing both molecular and biological techniques. The PCR‐RFLP technique was developed in order to detect the single point mutation, G1105S, occurring on the Pv CesA3 gene. The sensitivity was also studied using the leaf‐disc bioassay. Thirty‐three downy mildew‐infected leaf samples, collected from 2010 to 2013 from Italian vineyards, were used in the study. PCR‐RFLP revealed the presence of 7 resistant, 12 sensitive, 14 mixed (sensitive and resistant) mutation profiles. Effective concentration for 50% inhibition rate (EC50 ) calculated from the bioassays showed an EC50 < 1 mg l −1 for samples that showed sensitive profiles, while for those samples that had a mixed profile, EC50 ranged from <1 to >300 mg l −1, and values for resistant profiles ranged from 200·28 to >300 mg l −1 . The results suggest that P. viticola populations infecting Italian vineyards are under a selection pressure due to CAA‐based fungicide applications. Significance and Impact of the Study: We characterized Plasmopara viticola populations utilizing PCR‐RFLP technique to detect a point mutation known to cause resistance to carboxylic acid amides (CAA) fungicides. Sensitivity of these samples to the mandipropamid fungicide was assayed by a leaf‐disc method. In this work, we provide the first evidence about the presence of mandipropamid‐resistant populations of P. viticola from commercial vineyards in Italy. Improving the knowledge about development of resistant populations could enhance the current grapevine downy mildew management strategies and minimize the risk of the spread of mandipropamid and other CAA‐resistant populations. Abstract : Significance and Impact of the Study: We characterized Plasmopara viticola populations utilizing PCR‐RFLP technique to detect a point mutation known to cause resistance to carboxylic acid amides (CAA) fungicides. Sensitivity of these samples to the mandipropamid fungicide was assayed by a leaf‐disc method. In this work, we provide the first evidence about the presence of mandipropamid‐resistant populations of P. viticola from commercial vineyards in Italy. Improving the knowledge about development of resistant populations could enhance the current grapevine downy mildew management strategies and minimize the risk of the spread of mandipropamid and other CAA‐resistant populations.